Life Narratives, Creativity, and the Social in the Americas - Raussert, Wilfried; Rocha Teixeira, Susana; Banerjee, Mita; Behluli, Sofie; Ferrari, Anna; Gerhard, Atalie; Haas, Astrid; Hornung, Alfred; Mehring, Frank; Veauthier, Ines E.; Völz, Sabrina (American frictions, 2025)
Resorting to life narratives as a comprehensive umbrella term and embracing hemispheric American studies paradigms, this edited volume explores the interrelations between life narratives, the social world, creativity, and different forms of media to narrate and (re)present the self to see in which way these expressions offer (new) means of (self-) representation within cultural productions from the Americas. Creativity in the context of life narratives nourishes the act of narrating and propels among others the desire to link individual life stories with larger stories of social embeddedness, conditioning, and transformation thus pushing new forms of historiography and other forms of nonfictional writing. Accordingly, the creative impulse fuses individual and collective experience with a larger understanding of the social including the latter's local and global embeddedness. The contributions in this volume analyze the ways in which the dynamics, tensions, and reciprocities between narrative, creativity, and the social world unfold in life narratives from the Americas. In particular, this volume addresses scholars and students of life writing, cultural and literary studies, gender, disability and postcolonial studies with new insights into life narratives from the Americas